Benign copy number changes in clinical cytogenetic diagnostics by array CGH - Whitby, H. (S. Karger AG, 2009)
A database of apparently benign copy number variants (bCNVs) detected by a Spectral Genomics Inc./PerkinElmer BAC array platform has been maintained through the University of Utah Comparative Genomic Hybridization laboratory since 2005. The target population for this database represents 1,275 patients with abnormal phenotypes, primarily children referred for developmental delay and mental retardation. These bCNVs are independent of any identified copy number abnormality detected. The most common 35 bCNVs observed and their frequencies are reported here, and a subset of ten of the patients studied was evaluated on a new oligonucleotide CNV array set designed by Agilent Technologies. There was a 76% concordance of calls for these 35 bCNVs detected by both array platforms in the same patients. The higher resolution of the Agilent oligonucleotide array compared to the BAC array allowed determination of the precise breakpoints of the observed CNVs, in addition to documentation of additional CNVs of smaller sizes. As expected, observed CNVs and their frequencies were generally consistent with those of other previously published and available databases, including the Database of Genomic Variants (http://projects.tcag.ca/variation/). The availability of these data should assist other clinical laboratories in the evaluation of CNVs of unknown clinical significance.